Delamination and Surface Roughness Analyses in Drilling Hybrid Carbon/Glass Composite. Issue 10 (26th July 2016) - Tan, C. L.; Azmi, A. I.; Muhammad, N.
Abstract : Previous attempts at drilling of fibrous composites have been challenging due to the limited mechanical properties and presence of severe delamination damage at the top and bottom surfaces of the drilled hole. With the recent introduction of hybrid carbon/glass fiber reinforced polymer (HFRP) composites in both research literature and industrial applications, the need for evaluating their drillability is inevitable prior to their final usage. This is mainly because of the unique properties of HFRP composites as compared to the single-type FRP composites. Therefore, this paper aims to present a research initiative that will elucidate the high-range parametric effects of drilling control factors on delamination damage and surface quality. Taguchi methodology and statistical analysis of variance were applied to determine the performance of the drilling process. Experimental results revealed that delamination damage and surface quality values were strongly influenced by the feed and special tool geometries rather than the spindle rotational speed. Changes in the feed are likely to contribute to increase in the thrust force and strain rate on the workpiece. Confirmation tests have shown the closeness of the calculated values via a regression model and additive rule with the experimental values. This indicates that the regression model from the response surface can be employed to estimate delamination damage and surface roughness during drilling of HFRP composite.